2014
DOI: 10.1039/c3cc49054h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical self-assembly of a discrete hexagonal metallacycle into the ordered nanofibers and stimuli-responsive supramolecular gels

Abstract: A discrete hexagonal metallacycle decorated with multiple amide groups and long hydrophobic alkyl chains was constructed via [3+3] coordination-driven self-assembly, from which the ordered nanofibers and stimuli-responsive supramolecular gels were successfully obtained via hierarchical self-assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Reversible gel to sol transition could be achieved upon the addition and removal of bromide ions. Similarly, by employing the structurally similar 120° building block 261 in combination with a 120° diplatinum(II) acceptor 270, the authors synthesized hexagonal metallacycle 279(Figure 93b) 200. In mixed solvent systems, the metallacycle self-assembled into nanofibers and supramolecular organometallic gels, and exhibited bromide-induced reversible gel-sol phase transition via the disassembly and reassembly of discrete hexagonal metallocycles.…”
mentioning
confidence: 99%
“…Reversible gel to sol transition could be achieved upon the addition and removal of bromide ions. Similarly, by employing the structurally similar 120° building block 261 in combination with a 120° diplatinum(II) acceptor 270, the authors synthesized hexagonal metallacycle 279(Figure 93b) 200. In mixed solvent systems, the metallacycle self-assembled into nanofibers and supramolecular organometallic gels, and exhibited bromide-induced reversible gel-sol phase transition via the disassembly and reassembly of discrete hexagonal metallocycles.…”
mentioning
confidence: 99%
“…On the basis of the general principle of coordination-driven self-assembly, the size and shape of the final discrete metallacycles are mainly determined by the angle and symmetry of the selected building blocks . The formation of a discrete hexagonal metallacycle can be realized through the combination of three 120° donor building blocks and three 120° acceptor subunits . In this study, a new 120° dipyridyl donor 1 containing chain transfer agents (CTAs) (Scheme S1) and 120° di-Pt­(II) acceptors 2 and 3 were selected for the construction of discrete hexagonal metallacycles decorated with three CTAs moieties at the alternative vertexes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Yang and co-workers constructed a discrete hexagonal metallacycle 46 decorated with multiple amide groups and long hydrophobic alkyl chains via [3 + 3] coordination-driven self-assembly of the 1208 dipyridyl donor 45 decorated with multiple amide groups and long hydrophobic alkyl chains and 1208 di-Pt(II) acceptor 33 (Scheme 9). [52] Since the presence of multiple intermolecular interactions imposed by amide groups and long alkyl chains outside of the hexagonal metallacycle 46, hierarchical self-assembly behaviour was thus investigated. The gelation ability of metallacycle 46 in various organic solvents was conducted by the "stable to inversion in a test tube" method, which revealed that hexagonal metallacycle 46 could generate the translucent supramolecular metallogels in the mixed solvent of acetone and water (v/v, 2/1).…”
Section: Self-assembly Of Supramolecular Metallacycles For the Constrmentioning
confidence: 99%
“…Recently, Yang and co‐workers constructed a discrete hexagonal metallacycle 46 decorated with multiple amide groups and long hydrophobic alkyl chains via [3+3] coordination‐driven self‐assembly of the 120° dipyridyl donor 45 decorated with multiple amide groups and long hydrophobic alkyl chains and 120° di‐Pt(II) acceptor 33 (Scheme ) . Since the presence of multiple intermolecular interactions imposed by amide groups and long alkyl chains outside of the hexagonal metallacycle 46 , hierarchical self‐assembly behaviour was thus investigated.…”
Section: Functionalized Supramolecular Metallacyclesmentioning
confidence: 99%